Nitrogen-to-Oxygen abundance ratio variation in quiescent galaxies. Issue 1 (25th August 2018) - Yan, Renbin
ABSTRACT: For the first time, we establish a gas-phase abundance pattern calibration for quiescent galaxies using optical emission lines. Quiescent galaxies have warm ionized gas showing line ratios similar to low-ionization nuclear emission line regions. The ionization mechanism for the gas is still an unsettled puzzle. Despite the uncertainty in the ionization mechanism, we argue that we can still infer certain gas-phase abundance pattern from first principles. We show that the relative trend in N/O abundance can still be reliably measured based on [N ii ] λλ6548, 6583/[O ii ] λλ3726, 3729 and a direct measurement of the electron temperature. We construct a composite direct temperature tracer that is independent of extinction correction, by combining [O ii ] λλ3726, 3729/[O ii ] λ7320, 7330 and [S ii ] λλ6716, 6731/[S ii ] λ4068, 4076 and cancelling out the effect of extinction, as these involve the easiest-to-detect auroral lines in quiescent galaxies. With theoretical modelling, we establish the calibration for N/O based on [N ii ]/[O ii ] and a temperature tracer. We apply this technique to quiescent galaxies in the nearby Universe and find they span a range of 0.35 dex in N/O ratio from 17-percentile to 83-percentile of the whole distribution. These measurements can shed light on the chemical enrichment history of the warm ionized gas in quiescent galaxies.